Affective governance among street-involved women and their services providers. Issue 3 (2nd September 2019) - Dewey, Susan; Hankel, Jennifer; Brown, Kyria
ABSTRACT: Affect modulates and directs the governance of street prostitution in encounters between street-involved women and their social services and healthcare providers through three nodes on a circuit of affect. The first is the street, constituting a set of geographic and psycho-social phenomena that exert a formative and often intergenerational impact on street-involved women's lives. The second, selfhood, connects an understanding of trauma as inhibitory to cognitive development with the governmentality of mental health diagnoses. The third, embodied abjection, links the physical states and practices connected with addiction, homelessness, incarceration, and other forms of social suffering, with street-involved women's abjection.